Global security, safety and sustainability : the security challenges of the connected world : 11th International Conference, ICGS3 2017, London, UK, January 18-20, 2017, Proceedings /: the security challenges of the connected world : 11th International Conference, ICGS3 2017, London, UK, January 18-20, 2017, Proceedings. (2016) - Unknown
No abstract available